Medium-term effects of Ag supplied directly or via sewage sludge to an agricultural soil on Eisenia fetida earthworm and soil microbial communities - Courtois, Pauline (2022)
The widespread use of silver nanoparticles (AgNPs) in consumer products that release Ag throughout their life cycle has raised potential environmental concerns. AgNPs primarily accumulate in soil through the spreading of sewage sludge (SS). In this study, the effects of direct exposure to AgNPs or indirect exposure via SS contaminated with AgNPs on the earthworm Eisenia fetida and soil microbial communities were compared, through 3 scenarios offering increasing exposure concentrations. The effects of Ag speciation were analyzed by spiking SS with AgNPs or AgNO₃ before application to soil. SS treatment strongly impacted Ag speciation due to the formation of Ag₂S species that remained sulfided after mixing in the soil. The life traits and expression of lysenin, superoxide dismutase, cd-metallothionein genes in earthworms were not impacted by Ag after 5 weeks of exposure, but direct exposure to Ag without SS led to bioaccumulation of Ag, suggesting transfer in the food chain. Ag exposure led to a decrease in potential carbon respiration only when directly added to the soil. The addition of SS had a greater effect on soil microbial diversity than the form of Ag, and the formation of Ag sulfides in SS reduced the impact of AgNPs on E. fetida and soil microorganisms compared with direct addition.